2018
DOI: 10.1007/s10856-018-6129-2
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and histological comparison of carbonate apatite fabricated by dissolution–precipitation reaction and Bio-Oss®

Abstract: Carbonate apatite (COAp) is an inorganic component of bone. This study aimed to compare the composition and tissue response to of COAp (COAp-DP) fabricated by the dissolution-precipitation reaction using calcite as a precursor and Bio-Oss®, which is widely used in orthopedic and dental fields as a synthetic bone substitute. X-ray diffraction and Fourier transform infrared results showed that COAp-DP and Bio-Oss® were both B-type carbonate apatite with low crystallinity. The average sizes of COAp-DP and Bio-Oss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…In fact, Spence et al () reported that higher carbonate content led to an increased osteoclastogenesis and allowed resorption of the substitute in a dose dependent manner in vivo. Further, Fujisawa et al () reported that the size of the CO 3 Ap granules became smaller with implantation time in vivo. The resorption of bone or dissolution of apatite elevates Ca 2+ concentration since both bone and apatite are composed of calcium phosphate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, Spence et al () reported that higher carbonate content led to an increased osteoclastogenesis and allowed resorption of the substitute in a dose dependent manner in vivo. Further, Fujisawa et al () reported that the size of the CO 3 Ap granules became smaller with implantation time in vivo. The resorption of bone or dissolution of apatite elevates Ca 2+ concentration since both bone and apatite are composed of calcium phosphate.…”
Section: Discussionmentioning
confidence: 98%
“…The CO 3 Ap block fabricated in an aqueous solution upregulated osteoblastic differentiation of human bone marrow cells, and was resorbed by osteoclasts (Ishikawa, ; Kanayama et al, ; Nagai et al, ; Spence, Patel, Brooks, Bonfield, & Rushton, ). Fujisawa et al () reported that the CO 3 Ap showed faster bone formation especially in the cortical bone portion than Bio‐Oss, a bovine‐derived xenograft, at 8 weeks after implantation in the bone defect of a rabbit femur. These results clearly demonstrated the potential value of the CO 3 Ap block as an alternative to autografts.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were characterized as apatite without any other types of crystalline phases. Both samples had similar patterns, with pronounced peaks between 473 and 700 cm −1 [35], and absorption peaks ascribed to phosphatase band peaks at 962, 1051, and 1089 cm −1 (Figure 5). The results of the FTIR and XRD characterization analysis of sintered PGPT and porcine control particles agreed with a study done by Figueiredo et al which compared the physicochemical properties of bone substitutes used in dentistry vs. calcined human bone.…”
Section: Fourier Transform Infrared Spectroscopy Profilesmentioning
confidence: 80%
“…Compared with HA and β-TCP, carbonate apatite (CO 3Ap) can also be easily substituted for bone because its hydroxyl group is replaced with a carbonate group, and it therefore produces a skeleton has a porous microstructure that is morphologically similar to that of human cancellous bone 7) . CO3Ap granules show greater bone formation in the cortical portion of a bone defect than Bio-Oss, which is a deproteinized bovine bone mineral 8) . CO3Ap has also shown faster bone healing than HA via the activation of bone metabolism, which stimulates bone matrix formation by osteoblasts and bone absorption by osteoclasts 9) .…”
Section: Introductionmentioning
confidence: 96%